Phra Malai of Wat Thewa Sangkharam: : An Orthographic Analysis and Its Social and Cultural Connections Within the Local Context of Kanchanaburi - Phiromya, Jaturong; Luangdaeng, Phatchaya; hongsri, Kriangkri (Journal of Letters, 2025)
This research article aims to 1) analyze the Phra Malai manuscript of Wat Thewasangharam from a paleographic perspective, and 2) examine the interrelationship between this manuscript and the local society and culture of Kanchanaburi. A qualitative research methodology was employed, incorporating fieldwork data collection and documentary analysis and synthesis. The findings indicate that 1) the Phra Malai manuscript of Wat Thewasangharam is a Buddhist didactic text inscribed on white Thai folding books (samut thai khao), written in Khmer–Pali and Khmer–Thai scripts, and recorded in both Pali and Thai. The script characteristics correspond to the early to mid-Rattanakosin period, spanning the reigns of Kings Rama I to V, with the use of both full and subscript characters. Paleographic analysis reveals the use of Khmer–Pali, Khmer–Thai, and Thai scripts. The text is composed as chant poetry in six melodic modes: chan, choet, rap, mangkorn, wasant, and ekabot. When analyzed according to modern prosodic classification, the composition consists of 507 stanzas of kap yani 11, 248 stanzas of kap surangkhanang 32 (kap 32), 19 stanzas of kap chabang 16, and 10 stanzas of unidentified poetic forms resembling wasantadilok chan but deviating from conventional rules of heavy and light syllables. The manuscript was commissioned by Mae Phum and inscribed by Phra Thera Mai, with the primary purpose of instructing audiences on the law of karma, encouraging merit-making, almsgiving, moral discipline, and meditative practice, as well as imparting knowledge of hell and heaven. 2) In terms of its relationship with the local society and culture of Kanchanaburi, the Phra Malai manuscript of Wat Thewasangharam reflects the author’s worldview in five dimensions: the perceived meritorious benefits of transmitting and sustaining Buddhism in accordance with the roles and status of the Buddhist community; the influence of Buddhist culture in surrounding communities; the transmission of Buddhist literary traditions from Bangkok through monastic educational networks during the reign of King Rama V; the integration of traditional conventions with socio-cultural change mediated by educational practices in the same period; and the visualization of hell realms derived from the Phra Malai narrative as interpreted by mural painters.